Rheological characterization of low methoxyl pectin extracted from durian rind - Sze Hui Jong, Sze Hui Jong; Abdullah, Norazlin; Muhammad, Norhayati (Elsevier, 2023)
Pectin’s rheological properties are closely related to its functionality for food and pharmaceutical applications. In this study, the flow behavior and viscoelastic properties of durian rind pectin (DP) (esterification degree = 18.99%, molecular weight = 42.1 kDa) were evaluated at different concentrations (1.0–3.0% w/v), pH (2.0–6.0), and temperatures (flow behavior: 10–75 ◦C, viscoelastic properties: 5–90 ◦C). DP solutions had pseudoplastic behavior. The viscosities of DP solutions improved at rising concentrations and decreasing pH, whereas their viscosities dropped at increasing temperatures. The viscosities of commercial low methoxyl pectin (CLMP) solutions were greater than DP under the same conditions due to their greater molecular weight. DP gels, at a constant level of 50 mg Ca2+/g pectin and 30% sucrose (w/v), had greater gel strength at increasing pectin concentration and at a critical pH value (pH 3.0). The strongest gel was obtained at 3.0% (w/v) pectin concentration and pH 3.0, exhibiting greater gel strength than CLMP under the same condition. DP and CLMP gels remained gel-like throughout continuous heating and cooling, showing good thermal stability. Therefore, DP is a potential gelling and thickening agent for weak-acid-low-calorie food and pharmaceutical applications under a broad temperature range